Non-Orthogonal Multiple Access Assisted Device-to-Device Communication: Best Helping Base Station Approach - Huu-Phuc Dang; Minh-Sang Nguyen; Dinh-Thuan Do (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
It can be studied in this paper that a cooperative non-orthogonal multiple access (NOMA) helps device-to-device (D2D) communication system through base station (BS). In particular, we investigate BS selection scheme as a best channel condition for dedicated devices where a different data transmission demand on each device is resolved. The analysis on amplifying-and forward (AF) relay is proposed to evaluate system performance of the conventional cooperative NOMA scheme. Under the realistic assumption of perfect channel estimation, the achievable outage probability of both devices is investigated, and several impacts on system performance are presented. The mathematical formula in closed form related to probability has also been found. By implementing Monte-Carlo simulation, the simulation results confirm the accuracy of the derived analytical results. Also, the proposed D2D cooperative NOMA system introduces expected performance on reasonable selected parameters in the moderate signal to noise ratio (SNR) regime.